Experimental and theoretical investigations of a novel electret-based wave energy converter. (1st December 2022) - Fu, Yiqiang; Ruan, Haihui
Abstract: Motivated by carbon neutrality and subsea exploration, we propose a novel electret-based wave energy converter (WEC) achieving cost-effectiveness and high power-output. The WEC is mainly made of plastics (low cost) and is competent in achieving a long service life (no wearing parts). It demonstrates an exceptional average power density of 2.15 W m − 3, doubling the highest power density of ever reported WECs that are based on electrostatic induction and/or triboelectrification. The theoretical models of the energy conversion and dynamic stability of the proposed WECs have been established and validated by experimental results, which suffices for the optimization of the proposed WEC for practical applications. Moreover, it has been found that the average power of the encapsulated generator in the WEC is proportional to the diameter to the power of four, which invigorates model scaleups. Graphical Abstract: ga1 Highlights: A cost-effective and high-power-output electret-based wave energy converter (WEC) is proposed. Transverse instability can reduce power generation and can be predicted and modulated using Mathieu stability diagram. Validated theoretical models facilitate the optimization work in large-scale deployments. The average power output of the encapsulated generator in the (WEC) is proportional to the diameter to the power of four.